2021
DOI: 10.1002/hbm.25557
|View full text |Cite
|
Sign up to set email alerts
|

EEG and fMRI evidence for autobiographical memory reactivation in empathy

Abstract: Empathy relies on the ability to mirror and to explicitly infer others' inner states. Theoretical accounts suggest that memories play a role in empathy, but direct evidence of reactivation of autobiographical memories (AM) in empathy is yet to be shown. We addressed this question in two experiments. In Experiment 1, electrophysiological activity (EEG) was recorded from 28 participants. Participants performed an empathy task in which targets for empathy were depicted in contexts for which participants either di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…In our previous EEG experiment (Meconi et al, 2021), the size of the main effect of increased empathy ratings for AM compared with non-AM contexts was Cohen's d = 0.89, as obtained in a sample of mainly female participants (four males). The finding was replicated in the second fMRI experiment from the same project with Cohen's d = 0.51 as obtained in a sample composed of 11 males and 17 females.…”
Section: Power Calculationmentioning
confidence: 59%
See 3 more Smart Citations
“…In our previous EEG experiment (Meconi et al, 2021), the size of the main effect of increased empathy ratings for AM compared with non-AM contexts was Cohen's d = 0.89, as obtained in a sample of mainly female participants (four males). The finding was replicated in the second fMRI experiment from the same project with Cohen's d = 0.51 as obtained in a sample composed of 11 males and 17 females.…”
Section: Power Calculationmentioning
confidence: 59%
“…In two previous experiments from our laboratory (Meconi et al, 2021), we observed that participants judged their self‐perceived cognitive empathy as higher for individuals described to experience similar events as the participants experienced themselves when compared with non‐autobiographical memory (AM) contexts. Similarly, Bluck et al (2013) showed behavioral measures for increased explicit self‐perceived empathy when the observers (i.e., the participants) shared past experience of general physical pain with the person described in the task.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Along with other evidence ( Rütgen et al, 2015 , 2018 ), these findings are in line with those studies showing that incidental ( Forkmann et al, 2015 ) and voluntary ( Fairhurst et al, 2012 ) reinstatement of an autobiographical pain, involves the partial recruitment of the brain areas that encoded nociceptive stimuli at the time of memory formation. Indeed, memories of autobiographical physical pain augment participants’ cognitive empathy for other individuals depicted in similar physically painful situations ( Meconi et al, 2021 ).…”
Section: Perceiving the Physical And The Social Worldmentioning
confidence: 99%